STRATEGY DEVELOPMENT OF TOFU HOME INDUSTRY IN MASBAGIK DISTRICT IN EAST LOMBOK - Weni Elmayanti; Muhammad Anwar; Muhammad Nashruddin (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
The purpose of this study was to determine the strategy for developing a tofu home industry in Masbagik District, East Lombok Regency. The method used is descriptive, data collection techniques using survey techniques with direct interviews and questionnaires. The location of the research was determined by purposive sampling in three villages, namely South Masbagik Village, Danger Village, and East Masbagik Village. The data obtained were analyzed using SWOT. The results of the research are focusing on the S-O strategy to maintain the number of human resources by utilizing the nature of openness between the owner and employees and improving the experience in order to get satisfaction from the community for tofu products, maintaining affordable prices and expanding market share by taking advantage of limited competitors and high public awareness of consuming tofu.